Small & Medium Enterprises and Sustainable Economic Development - Festus Edobor (International Journal of Small and Medium Enterprises and Business Sustainability, 2023)
Small and medium enterprises (SMEs) have been a driving force in poverty alleviation. One of the key areas of the Sustainable Development Goals (SDGs) is poverty alleviation. Poverty is a major problem in Nigeria and one of the ways to alleviate poverty is through deliberate job creation through SMEs. The dimension of poverty alleviation in the SDGs goals has been an area where SMEs have played a pivotal role. This paper reviewed SMEs’ role in realizing the SDGs. Many challenges affect how we can better achieve SDGs as highlighted in this paper. The factors that affected our poor performance during the Millennium Development Goals (MDGs) which include unmanageable population, pervasive poverty, ignorance and superstition, religious dogmatism, corruption and economic mismanagement, lack of political will, and authenticity of collected data are still largely within Nigeria. It was concluded that SMEs should be empowered in other to help achieve the SDGs in Nigeria.